2019
DOI: 10.1002/ecs2.2974
|View full text |Cite
|
Sign up to set email alerts
|

Timing to temperature: Egg‐laying dates respond to temperature and are under stronger selection at northern latitudes

Abstract: Global climate change produces spatially variable patterns of environmental change. This could put migratory species at risk as the synchrony between migration timing and suitable breeding conditions could become mismatched. For migratory birds, whether the timing of egg laying is a plastic trait that can vary in response to environmental change has been sparsely studied across regions and systems and thus remains poorly known. We investigated the effects of temperature variability and climate warming on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Prothonotary warblers do not belong to either of these categories of vulnerable species. Similarly, breeding earlier in warmer years with no apparent cost to reproduction has been documented in many other migratory bird species including reed warblers (Halupka et al, 2008), tree swallows (Dunn et al, 2011), purple martins Progne subis (Shave et al, 2019), and black-throated blue warblers (Townsend et al, 2013). In each of these study systems, authors suggested that earlier breeding was not costly, in part, because food resources (i.e., insects) were available enough to accommodate it.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Prothonotary warblers do not belong to either of these categories of vulnerable species. Similarly, breeding earlier in warmer years with no apparent cost to reproduction has been documented in many other migratory bird species including reed warblers (Halupka et al, 2008), tree swallows (Dunn et al, 2011), purple martins Progne subis (Shave et al, 2019), and black-throated blue warblers (Townsend et al, 2013). In each of these study systems, authors suggested that earlier breeding was not costly, in part, because food resources (i.e., insects) were available enough to accommodate it.…”
Section: Discussionmentioning
confidence: 74%
“…To the contrary, a growing body of research is finding that warming in temperate latitudes associated with global climate change is advancing the timing of clutch initiation in several species of migratory birds (e.g., Winkler, 1999, 2010;Both et al, 2004;Mazerolle et al, 2011;Tomotani et al, 2018). Earlier nesting may be a byproduct of temperaturerelated advances in plant and insect phenologies experienced by birds upon arrival at breeding grounds (Townsend et al, 2013;Shave et al, 2019). However, earlier breeding can cause reductions in reproductive success if the timing of breeding creates a mismatch between seasonal pulses in critical resources (Both et al, 2010) (i.e., food) and peak demand for feeding young (Visser and Gienapp, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the number of fledglings and probability of obtaining recruits are fitness components much more related to females and thus the fitness benefits of early arriving for males must be because for instance early arriving males pair with early laying females (Saino et al, 2004;Cooper et al, 2010;Tomotani et al, 2017) or occupy higher quality territories. Thus, the fitness consequences of male arrival time may (partly) arise through correlation with female timing, especially female breeding time, which is related to reproductive success and to local environmental conditions (Dunn and Winkler, 1999;Townsend et al, 2013;Visser et al, 2015;Tomotani et al, 2018;Shave et al, 2019).…”
Section: Fitness Benefits Via Femalesmentioning
confidence: 99%
“…Evidence of the impact of recent climate change on phenology of animals and plants is ample today (Both et al, 2006;Dunn & Winkler, 1999;Hällfors et al, 2020;Helm et al, 2019;Parmesan & Yohe, 2003;Root et al, 2003;Saino et al, 2011;Schwartz et al, 2006;Shave et al, 2019;Townsend et al, 2013), but the underlying mechanisms of the changing patterns are poorly understood (Knudsen et al, 2011), especially considering the variation of climate change with latitude (Parmesan, 2007). In birds, phenological shifts, like advancement of breeding time due to warmer and earlier springs, may facilitate larger clutches and the opportunity to rear more young (Dunn, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Still, some studies at northern sites experienced more stable spring and summer temperatures during the last decades (Ram et al, 2019) or even temperature decrease (Both et al, 2004;Both & Marvelde, 2007) finding nonsignificant trends on breeding time change in several bird species. Nevertheless, studies on the effect of climate change on breeding time and breeding success over a large latitudinal gradient are scarce (Parmesan, 2007; but see examples in Dunn & Winkler, 1999;Hällfors et al, 2020;Meller et al, 2018;Shave et al, 2019) and need further investigation.…”
Section: Introductionmentioning
confidence: 99%